Therapeutic effects of medicinal and food-based traditional herbal couples on type 2 diabetes mellitus based on pharmacodynamics and pharmacokinetics - Yuhang Xu; Jing Li; Mengyao Cui; Xiaoliang Li; Hongyan Zhai; Deling Wu; Deling Wu; Deling Wu; Xiaoqin Chu; Xiaoqin Chu; Xiaoqin Chu; Xiaoqin Chu (Frontiers in Pharmacology)
IntroductionCinnamomi Ramulus (CR) is the dried bark of Cinnamomum cassia Presl, Lauraceae. Puerariae Lobatae Radix (PLR) is the dried root of the Pueraria lobata (Wild.) Ohwi, Leguminosae. This Chinese herb couple come from the classic formula “Gui Zhi Ge Gen Tang,” which is included in the TCM classic “Treatise on Febrile Diseases.” Our previous studies have found that CR related herbal compound and PLR related herbal compound are useful in improving type 2 diabetes mellitus (T2DM), which is expected to be an antidiabetic candidate with fewer side effects. However the mechanism of action of CR-PLR on T2DM has not yet been fully elucidated.MethodsThe decoction of CR-PLR was prepared by aqueous extraction method and the composition of it was analyzed using UPLC-Q-TOF-MS and HPLC. The T2DM model was established by intraperitoneal injection of streptozotocin, and the groups of drug administration were metformin, CR, PLR and CR-PLR groups, with continuous gastric gavage for 6 weeks, and the serological indexes were detected by ELISA. The abundance of rats’ gut flora was detected by 16s rDNA sequencing, and changes in the content of short-chain fatty acids (SCFAs) in feces of rats were detected by GC-MS; and the expression of G protein-coupled receptor43 (GPR43) and glucagon-like peptide-1 (GLP-1) proteins in colonic tissues of rats were detected by Western Blot. The pharmacokinetic behavior of CR-PLR was investigated in both normal and T2DM model rats. Caco-2/HT29 co-culture cell model was established in vitro, transepithelial electrical resistance (TEER) and ALP activity of epithelial cells were measured to evaluate cell model integrity and cell polarization, Alcian blue staining was used to verify the presence of mucus production, and CCK-8 was used to screen drug safe concentration. The bidirectional transport of puerarin was studied to investigate the transport mechanism of puerarin and the effect of leuric acid on puerarin transport.Results and discussionThe results indicated that CR-PLR can stimulate intestinal flora, increase the content of SCFAs, activate intestinal GPR43 protein, and promote the secretion of GLP-1 in intestinal L cells, which plays a therapeutic role in the treatment of T2DM. Additionally, cytology and pharmacokinetics experiments have proved that cinnamic acid (CA) can enhance the absorption and transport of puerarin (PUR) by inhibiting the efflux effects mediated by P-gp and MRP efflux transporters. The present study exhibites the scientific and reasonable menaning of this novel Chinese herb couple treating T2DM from the perspecives of pharmacodynamics and pharmacokinetics.